Implementasi Pembelajaran Berbasis Kecerdasan Buatan di Sekolah Dasar - Purnama, Purnama; Muharani, Irma Nur; Patras, Yuyun Elizabeth (Universitas Negeri Padang, 2024)
This research is motivated by the low motivation and learning outcomes of students in elementary schools and aims to determine trends in artificial intelligence-based research and implementation as well as the influence of artificial intelligence on students' motivation and learning outcomes in elementary schools. The research method used is the SLR method by the PRISMA. This research was conducted through the PoP application with the database used is Google Scholar 2018-2023 with the keyword